Transformasi Digital Dalam Rangka Mendukung Penerapan Sistem Jaminan Halal Berdasarkan Pernyataan Pelaku Usaha (Studi Kasus Di IKM Es Krim XYZ) - Murti, Hari Wisnu (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
In order to increase the competitiveness of small and medium industries, it is necessary to increase the capacity of IKM in all business value chains. The government has imposed mandatory halal certificates for products in the region as a form of guarantee for halal products. For this reason, in order to encourage the competitiveness of IKM by penetrating the market through halal product guarantee certification, it is necessary to identify the conformity of the production of IKM XYZ with the Halal Product Assurance System for Micro, Small, and Medium Entreprises (MSMEs) based on the Circular Letter of the Head of the Halal Product Assurance Organizing Agency Number B-5952/BD.II./P.II.I.2/HM.00/09/2021. The following case study research was carried out using the method of identifying the initial conditions of IKM XYZ through interviews, then conducting an assessment of the Decree of the Head of the Halal Product Guarantee Agency Number 33 of 2022. Based on the identification results, it was determined that improvement was needed on the halal traceability aspect which had an impact on the inspection of the arrival of materials; transportation and distribution of materials and products; and Product launch/sales. In line with the Making Indonesia 4.0 policy that digital transformation is carried out in order to meet sustainability standards, the findings of improving the halal process are carried out by adopting digitalization. For this reason, digitization is carried out in digital bookkeeping activities to meet the criteria for halal guarantees in the form of a cloud-based data center. Based on the discussion conducted, it was concluded that the application of database technology based on number processing and cloud storage can provide answers to the findings of identification of halal product guarantees.